Archaism in the constitution - Gansukh, Ariun-Onon (Mongolian Language and Literature Studies, 2024)
The lexicon of a language is constantly changing along with the evolution of social development, and old words and expressions that indicate phenomena are removed from the vocabulary, and new phenomena and developments enrich the vocabulary of the language with new words and expressions. In other words, on the one hand, the use of words is reduced and transferred to the ranks of old words, on the other hand, some words that were considered archaic words are included in the neologism resources. Mongolian words can be classified into active and passive according to their active use, and active words can be classified as highly active or colloquial words, and ordinary active or commonly used words. Commonly used words are words that make up the majority of the vocabulary, serve all professions equally, and describe import ant phenomena of human social relations and life, and are called active words. Passive words are words that are not often used by the general public and are used by certain professional groups. The passive vocabulary of the Mongolian lan guage includes local dialect words, vulgar words, professional and terminological words, new and old words, etc. This article presents observations on the archaism of the constitution. Үндсэн хууль дахь хуучирсан үгийн тухай Хураангуй: Хэлний үгийн сан нь нийгмийн хөгжлийн хувьслыг даган байнга өөрчлөгддөг бөгөөд зарим үг хэллэгийн хэрэглээ нь хязгаарлагдаж идэвхгүй үгийн санд орж байхад яг эсрэгээрээ шинэ юм үзэгдэл, ойлголт, ухагдахууныг заасан шинэ үг хэллэг бий болж сэлбэгдэн баяжиж байдаг. Монгол хэлний үгийг идэвх, хэрэглээгээр нь идэвхтэй ба идэвхгүй гэж ангилж идэвхтэй үгийг нэн идэвхтэй буюу ярианы хэлний үг, жирийн идэвхтэй буюу түгээмэл хэрэгцээт үг гэж ангилдаг. Түгээмэл хэрэгцээт үг гэж үгийн сангийн ихэнх хувийг бүрэлдүүлдэг, бүх насны бүхий л мэргэжлийн хүмүүс мэдэж хэрэглэдэг, хүний нийгмийн харилцаа, амьдралын түгээмэл үзэгдлийг заан нэрлэсэн үгийг хэлнэ. Харин хүмүүс тэр бүр хэрэглэдэггүй, тодорхой мэргэжлийн бүлэг хүмүүсийн хэрэгцээт үг хэллэгийг идэвхгүй үг гэнэ. Монгол хэлний идэвхгүй үг хэллэгт нутгийн аялгууны үгс, этгээд бүдүүлэг үгс, мэргэжлийн болон нэр томьёоны үг, шинэ ба хуучин үг зэрэг хамруулж үздэг. Энэ өгүүлэлд 1924, 1940, 1960 оны үндсэн хуулийн хуучин үг хэллэгт хийсэн ажиглалтыг танилцуулна. Түлхүүр үгс: хуулийн үг хэллэг, хуучин үг, түүхэн үг, үндсэн хууль